Nevoid Basal-Cell Syndrome: literature review and case report in a family - Tincani, Alfio José; Martins, Antônio Santos; Andrade, Ricardo Gomes; Mello Jr. , Edgar José Franco; Marco Antônio Camargo, (São Paulo Medical Journal, 1995)
The Nevoid Basal-Cell Carcinoma Syndrome (NBCC), or as it is also referred to, basal-cell nevus syndrome or Gorlin-Goltz syndrome, is characterized by multiple early-appearing basal cell carcinomas, keratocytosis of the mandible, and anomalies of the ocular, skeletal reproductive system. We describe four patients in the same family, all of them possessing a large number of skin tumors associated with other typical clinical and X-Ray anomalies of NBCC. The definitive treatment of NBCC has yet to be established, however, early diagnosis is very important as well as the periodical follow-up examination of ten patients, mainly due to the transformations in the skin lesions that may occur.